Tailor-made approach for quadricuspid aortic valve repair. (May 2014) - Shimamoto, Takeshi; Komiya, Tatsuhiko; Maruo, Takeshi; Sakaguchi, Genichi
We describe the successful repair of a quadricuspid aortic valve in a 64-year-old man after attempted tricuspidization via detachment of a commissure of the accessory cusp failed. Bicuspidization via detachment of another commissure was successful. Quadricuspid aortic valve repair by bicuspidization, which surgically transforms 3 cusps into 1, may be a simple and reproducible technique if tricuspidization repair has failed.